Synthesis and Structural Characterisation of Some New Ternary Complexes of Co(II and III) and Ni(II) - K. Agarwal, Suresh; Chand, Subhash (Asian Journal of Chemistry, 2010)
Ternary complexes of Co(II and III) and Ni(II) with isonitrosoacetophenone isonicotinic hydrazide (INAPIH)/isonitrosoacetophenone furoic hydrazide (INAPFH) as primary and 1-(o-methoxy anilinomethyl) benzimidazole (MAMB) as secondary ligand have been synthesised and characterised on the basis of analytical, conductance, spectral and TG data.